Dawah Through Effective Educational Strategies: A Perspective from the Qur'an, Surah An-Nahl, Verse 125 - Nurwa hida; Abdur Razzaq; Kristina Imron (The Future of Education Journal, 2025)
This study examines dawah strategies through education based on Surah An-Nahl (16:125), which emphasizes three main methods: wisdom (hikmah), good advice (mau‘izhah hasanah), and dialogue in the best manner (mujadalah billati hiya ahsan). A qualitative approach with a literature study method was employed, with primary data sourced from the Qur'an and its interpretations, and secondary data from recent academic literature from 2021 to 2025. The research population includes dawah and Islamic education literature, with a purposive sample considering the challenges of modern digitalization. Content analysis techniques were applied to interpret meanings in the context of education. The results indicate that Qur'anic dawah methods are highly relevant and aligned with effective Islamic education practices, emphasizing wisdom in teaching, moral exemplification, and critical dialogue. The study concludes that integrating these values into education can support the continuity of dawah in the modern era.